Development of polyclonal antibodies-based serological methods for detection of the rehmannia mosaic virus in field plants - Chen, Jiahuan; Feng, Chenwei; Guo, Xiao; Zhou, Yuchen; Gu, Tianxiao; Zhuang, Xinjian; Cheng, Lei; Zhang, Kun (Frontiers in Sustainable Food Systems, 2022)
Rehmannia glutinosa is a top-grade traditional Chinese medicine, and also is an important planting medicinal material for Chinese poor farmers shaking off poverty. Rehmannia mosaic virus (ReMV) causes big economic loss of R. glutinosa in planting area. However, there is no effective methods for quick, accurate, and high-throughput detection for ReMV in Chinese production area. The preserved R. glutinosa samples carrying ReMV was taken for research material. The coat protein coding sequences (CPReMV) was cloned and sequenced. The target sequence was further placed into a prokaryotic expression vector to express the N-terminal-tagged recombinant CPReMV protein (His-CPReMV). Purified His-CPReMV was used as an antigen to immunize New Zealand white rabbits, and antiserum was obtained. The titers and sensitivities of the antisera were analyzed and evaluated. Polyclonal antibodies were purified from the antiserum, and the titers and sensitivity to the target His-CPReMV protein were evaluated. The results demonstrate that the obtained polyclonal antibodies against His-CPReMV could be successfully used for rapid, accurate, and high-throughput detection of ReMV from R. glutinosa planted in the wild. Our investigation established serological-based detection methods for ReMV for the first time, and provides a foundation for future exploration of the pathogenic mechanisms of ReMV in R. glutinosa.